If is a complex number, then the sum of the roots of the equation equals to:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using the property ∣ z ∣ 2 = z . z
we can rewrite the equation as z 3 + z 2 − z z + 2 z = 0 ⟺ z ( z 2 + z − z + 2 ) = 0 (as we see, zero is a root)
Let z = a + b i ; i = − 1 and a , b real numbers.
Then we can rewrite the equation as:
( a + b i ) 2 + ( a + b i ) − ( a − b i ) + 2 = 0 ⇔ a 2 − b 2 + 2 a b i + 2 b i + 2 = 0
Hence:
a 2 − b 2 + 2 = 0 (real part) ∧ 2 a b + 2 b = 0 (imaginary part)
From the imaginary part:
→ First case: b = 0 then a 2 + 2 = 0 and there are no solutions.
→ Second case: b = 0 ⟹ a = − 1 . then: 1 − b 2 + 2 = 0 and b = ± 3 ∴ Solutions: z = − 1 ± i 3
Summing it up: S = − 2